Posttraumatic Growth and Resilience after A Prolonged War: A Study in Baghdad, Iraq - Heyder Kamil Mahdi; Kususanto Prihadi; Shahabuddin Hashim (International Journal of Evaluation and Research in Education (IJERE), 2014)
This study investigates the causal relationship between resilience and posttraumatic growth (PTG) among Iraqi students who are exposed to traumatic events especially after the war in 2003. A survey has been conducted among 450 students from the colleges of political science, media, science, and veterinary medicine at the University of Baghdad in academic year 2013 to 2014. Participants completed a survey that consisted of the Baghdad Trauma History Screen, Post-traumatic Growth Inventory, and Connor–Davidson Resilience Scale. Results indicate a significant positive influence of resilience on PTG. Implications of the results and recommendations for further research are discussed. DOI: http://dx.doi.org/10.11591/ijere.v3i3.6316